One-Step Electrodeposition of Superhydrophobic Coating on 316L Stainless Steel - Andrea Zaffora (MDPI AG, 2021)
Superhydrophobic coatings were fabricated through a one-step electrochemical process onto the surface of 316L stainless steel samples. The presence of hierarchical structures at micro/nanoscale and manganese stearate into the coatings gave superhydrophobicity to the coating, with contact angle of ~160°, and self-cleaning ability. Corrosion resistance of 316L samples was also assessed also after the electrodeposition process through Electrochemical Impedance Spectra recorded in an aqueous solution mimicking seawater condition.